Building blocks of agriculture - Heever, Jurie van den (HTS teologiese studies, 2022)
The origins of agriculture lie in the distant past, approximately 12 000 years ago, when hunter-gatherers of the Palaeolithic embraced sedentism at the dawn of the Neolithic. The variety of life history transitions emanating from this unique phenomenon have had an enormous impact on the biodiversity of the planet, while subjecting humanity to a variety of life-changing physical and social challenges right up to the present. The ever-present consequences of the Agricultural Revolution continue to demand our attention, yet frustrate our efforts, on a seemingly perpetual basis, to effectively manage the outcomes. Here we review the origins and lasting after-effects of the Agricultural Revolution and its impact on the human condition, with reference to sedentism, nutrition, health issues, disease, gender discrimination as well as mythmaking and religion.Contribution: Our aim is to engage a wider audience with respect to the causes and consequences of the Agricultural Revolution. We discuss a broad spectrum of relevant phenomena implicated in this epochal event and consequently underline that the Agricultural Revolution precipitated not only major changes to the ecology of the planet, but also and most importantly to the social and cultural well-being of humanity.